PROCEDURE TO OVERCOME DENTAL ANXIETY IN CHILDREN WITH AUTISM SPECTRUM DISORDER: A LITERATURE REVIEW - Alfini Octavia (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2020)
Introduction. Dental anxiety in children with Autism Spectrum Disorder(ASD) is challenging for dentists and dental staff. Children with autism usually show negative behavior toward dental treatment due to their limitations in social interaction, language, and communication. Consequently, the necessary dental procedure could not perform. Some procedures could be conducted to overcome dental anxiety. The purpose of this review is to report the relevant studies about the procedure to overcome dental anxiety to children with  Autism Spectrum disorder.Main body. Relevant articles during the year 2010- March 2020  were identified and retrieved from three internet databases  PubMed and  Cochrane. Through removing duplicates, title and abstract screening and applied inclusion criteria and exclusion criteria were also applied to the journals to find eligible studies.  Nine articles that were finally eligible to recommend the procedure that reduces the dental anxiety for the children with ASD.Conclusion. It can be concluded that the structural and visual approach and long-term follow-up of children with autism is the recommended approach to overcome dental anxiety.